1989
DOI: 10.1007/bf01883858
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the new class I antiarrhythmic agent diprafenone on the end-systolic pressure-volume relationship (conductance technique)

Abstract: To evaluate cordiodepressive risks of antiarrhythmic treatment with diprafenone, we monitored, in addition to conventional hemodynamic parameters, end-systolic pressure-volume relations to assess potential negative inotropic effects. Thirteen patients underwent hemodynamic analysis with and without the influence of diprafenone 1.5 mg/kg, both a) at rest (paced heart rate of 90 beats/min and b) during tachycardia (paced tachycardia of 160 beats/min). Left ventricular volumes increased under the influence of dip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Binding experiments using radioactively labeled toxins indicate that DPI 201-106 and its enantiomers do not interact with sites already identified for tetrodotoxin or sea anemone and scorpion toxins. (30). The positive inotropic effect of DPI appears to be due to an effect of the drug on the myocardial Na+ channel (1)(2)(3).…”
mentioning
confidence: 99%
“…Binding experiments using radioactively labeled toxins indicate that DPI 201-106 and its enantiomers do not interact with sites already identified for tetrodotoxin or sea anemone and scorpion toxins. (30). The positive inotropic effect of DPI appears to be due to an effect of the drug on the myocardial Na+ channel (1)(2)(3).…”
mentioning
confidence: 99%
“…LV muscle mass was calculated according to Rackley et al [6] with the modification indicated by Trenouth [7], Simultaneous LV volume and LV pressure relations were per formed by a conductance catheter, a discriminative QRS-analysis of ECG and a signal-analysis computer system 'Orpheus IF. The method is described in detail elsewhere [8][9][10]. Since conductance correlated with hemoglobin (r=0.84), values were corrected to patients' hemo globin.…”
Section: Invasive Studymentioning
confidence: 99%